Laparoscopic Ventral Mesh Rectopexy (LVMR) - an Early Experience in Birdem Hospital - Ratan, Md Ezharul Haque; Alam, Hasina (Bangladesh Critical Care Journal, 2018)
Background : Full thickness rectal prolapse are treated by multiple procedures through perineal and abdominal approach. Consensus is lacking as to the best option. Each procedure is associated with significant recurrence rate. Objective : The aim of this study is to report the effectiveness, complications following laparoscopic ventral mesh rectopexy in patients with full thickness rectal prolapse. Methods : The study is a retrospective evaluation of 6 consecutive patients by a single attending surgeon in a general and laparoscopic surgery unit,between July 2014 to June 2016. Peritoneum was incised at the pouch of Douglas or rectovesical pouch, space created between the rectum and the vagina or urinary bladder, polypropylene mesh was fixed to the rectum with non-absorbable suture and to the promontory of the sacrum with same suture instead of staples. In females, the mesh was also fixed anteriorly with posterior fornix of vagina. The peritoneum was suture closed over the mesh. Patients were reviewed at 1 and 6 months, then annually to assess recurrence, morbidity and mortality. Result : There was no recurrence or mortality among four female and two male patients. Morbidity consistedof chronic deep perineal pain in one youngmale patient who was treated conservatively with oral analgesic. Conclusion : LVMR seems to emerge as a safe and effective procedure to treat full thickness rectal prolapse, but large series and long term results are needed and we are continuing the study for the same. Bangladesh Crit Care J September 2018; 6(2): 71-73